Efek suplementasi tepung kulit jengkol pada pelepah sawit fermentasi terhadap profil mikroba rumen dan produksi gas metan in vitro - Nurhaita Nurhaita; Nur Hidayah; Neli Definiati (Universitas Sebelas Maret, 2021)
Objective: This research was aimed to evaluation the effect of supplementation jengkol peel powder in fermented oil palm fronds on rumen microbes profile and methane production on in vitro.Methods: The used design was factorial randomized block design with four treatments supplementation of jengkol peel powder at 0, 2, 4, and 6% and four groups as replications. The observed variables were rumen microbes profile (population of total bacteria, cellulolytic, and protozoa), methane production, partial volatile fatty acid (VFA) proportion and acetate/propionate (A/P) ratio. The data were analyzed using ANOVA and different among treatments means examined by Duncan Multiple Range Test (DMRT).Results: The result showed that supplementation of jengkol peel powder at 6% substrate increased (P<0.05) total and cellulolytic bacteria population. Jengkol peel powder supplementation as much as 4 and 6% decreased (P<0.05) protozoa population, methane production, acetate proportion and A/P ratio. Supplementation of jengkol peel powder at 2% increased (P<0.05) propionate production.Conclusions: In conclusion, fermented oil palm fronds can be substituted with jengkol peel powder at 2% substrate that did not disturb rumen microbes profile, decreased methane production, acetate proportion, A/P ratio and increased propionate production on in vitro.